2016
DOI: 10.1007/s00253-016-7476-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucansucrase Gtf180-ΔN of Lactobacillus reuteri 180: enzyme and reaction engineering for improved glycosylation of non-carbohydrate molecules

Abstract: Glucansucrases have a broad acceptor substrate specificity and receive increased attention as biocatalysts for the glycosylation of small non-carbohydrate molecules using sucrose as donor substrate. However, the main glucansucrase-catalyzed reaction results in synthesis of α-glucan polysaccharides from sucrose, and this strongly impedes the efficient glycosylation of non-carbohydrate molecules and complicates downstream processing of glucosylated products. This paper reports that suppressing α-glucan synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 33 publications
8
29
0
Order By: Relevance
“…S2 ). With sucrose as donor substrate, GtfA-ΔN, Gtf180-ΔN, and GtfMLI-ΔN also efficiently glucosylated the phenolic compounds resorcinol, pyrogallol, and ethyl gallate (data not shown) and used their mono-glucosides, resG1 (Devlamynck et al 2016 ), pyrG1 (Supplemental material, Table S1 and Fig. S3 ), and etgaG1 (Supplemental material, Table S1 and Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…S2 ). With sucrose as donor substrate, GtfA-ΔN, Gtf180-ΔN, and GtfMLI-ΔN also efficiently glucosylated the phenolic compounds resorcinol, pyrogallol, and ethyl gallate (data not shown) and used their mono-glucosides, resG1 (Devlamynck et al 2016 ), pyrG1 (Supplemental material, Table S1 and Fig. S3 ), and etgaG1 (Supplemental material, Table S1 and Fig.…”
Section: Resultsmentioning
confidence: 98%
“…α- d -Glc p -catechol (catG1) and α- d -Glc p -(1→4)-α- d -Glc p -catechol (cat 4 G2) synthesized by GtfA-ΔN (te Poele et al 2016 ), and α- d -Glc p -(1→3)-α- d -Glc p -catechol (cat 3 G2) and α- d -Glc p -(1→6)-α- d -Glc p -catechol (cat 6 G2) synthesized by Gtf180-ΔN (Devlamynck et al 2016 ), were isolated and purified using preparative normal-phase HPLC (NP-HPLC) as described previously (te Poele et al 2016 ). GtfA-ΔN enzyme activity on catG1 was measured at six different catG1 concentrations ranging from 3.1 to 100 mM using 0.125 mg/mL GtfA-ΔN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects were observed in studies where maltose was used as acceptor substrate, 35 or even when non-carbohydrate compounds were used as acceptor substrates. 6 The crystal structure of GTF180-ΔN in complex with maltose revealed that N1029 is involved in a hydrogen bond network with the nonreducing end glucosyl moiety of maltose in subsite +1, making direct and indirect hydrogen bonds with its C3 and C4 hydroxyl groups. 18 Mutant N1029G, when it acts on lactose as an acceptor substrate, added an (α1→3)-linked Glc moiety to compounds F2–F5 of the GL34 mixture to synthesize G1–G4 (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…The design of enzymes with specific features aimed at new acceptor substrates, to better control regioselectivity and/or to increase the reaction yield contributes to enhance the glycodiversification and quality of the attained products [15,16]. Protein engineering approaches have led to major achievements to create novel enzymes [17], and to improve their performance (i.e., productivity, activity, and pH and thermo-stability) [18].…”
Section: Current and Future Trends In Production Of Prebiotic Oligosamentioning
confidence: 99%